Consumer Engagement with Retail Firm through Social Media - Salim, Siti Aisyah; Hasan, Nur’ Ain Fatehah (Research in Management of Technology and Business, 2021)
Social media has gained significant attention as people spend most of their time on these platforms. This has motivated retail firms to change their marketing strategies and engage with consumers through social media. Consumer engagement is important for helping retail firm to enhance their relationship with consumers as well as promoting their new products. Though there are several studies looked into consumer engagement but there is still a lack of studies looking into consumer engagement with retail firm through social media. Thus, this study aims to examine the relationship between consumer engagement and intention to engage with retail firm social media. This study used Theory of Reasoned Action (TRA) and Technology Acceptance Model (TAM) to examine these relationships. Data has been collected from 120 social media users in Johor Bahru city using quantitative approach and online survey. Data has been analyzed using Statistical Package for Social Science (SPSS) software to get the demographic information, variables, and the relationship between the variables. This study helps retailers and consumers to improve the awareness on consumer engagement towards social media. From the analysis, it showed that the level of perceived enjoyment, peer communication and perceived usefulness towards intention to engage are in average level. Among all these variables, perceived usefulness has the highest average mean score with 3.40. In term of relationship, all three variables which are perceived enjoyment, peer communication and perceived usefulness have a positive significant relationship towards intention to engage with correlation coefficient of 0.395, 0.293 and 0.655.